Pengaruh Good Corporate Governance (GCG) Dan Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan Perbankan Yang Terdaftar Di Indonesia Stock Exchange (IDX) - Anisa Dewi Puspita; Tina Kartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is to determine whether there is an effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on the financial performance of banks listed on the Indonesia Stock Exchange (IDX) in 2019-2021. This study aims to influence; 1) Effect of GCG with audit committee indicators on financial performance (ROA), Effect of CSR on ROA, and 3) Effect of GCG and CSR on ROA. The variables used in this study are the independent variable and the dependent variable. This research is a research that uses quantitative research methods. The population and sample in this study are the company's financial ratio reports. In this study, the writing used data collection techniques with secondary data. Using statistical methods. The results showed that; 1) The audit committee has no positive and significant effect on banking financial performance, 2) Corporate Social Responsibility has no effect on banking financial performance, 3) the audit committee and Corporate Social Responsibility simultaneously (simultaneously) affect financial performance. Keywords : Good Corporate Governance, Audit Committee, Corporate Social Responsibility, Return On Assets.